Stabilization and dispersion of carbon nanomaterials in aqueous solutions: A review - Al-Hamadani, Y.A.J.; Chu, K.H.; Son, A.; Heo, J.; Her, N.; Jang, Min; Park, C.M.; Yoon, Y. (Elsevier, 2015)
Carbon nanomaterials (CNMs) have become candidates for numerous applications in nanocomposites, microelectric devices, sensors, energy storage, microelectronics, biomedicines, and mechanical resonators. However, a key challenge is how to enhance the dispersion and stabilization of CNMs in water. Thus, this review summarizes recent progress on the stabilization and dispersion of various CNMs (such as carbon nanotubes, graphene (oxides), and fullerenes) in aqueous solutions. The stabilization and dispersion of target CNMs is reviewed to address the effects of water quality conditions (pH, ionic strength, temperature), natural/synthetic dispersing agents, and the effects of ultrasonication, acidification, and/or UV irradiation on dispersion and stabilization. Applications of CNMs are also briefly addressed regarding removing micropollutants by adsorption in water and wastewater treatment. The outlook for future research challenges on CNMs is also discussed. (C) 2015 Elsevier B.V. All rights reserved.